Down-regulation of DNA key protein-FEN1 inhibits OSCC growth by affecting immunosuppressive phenotypes via IFN-γ/JAK/STAT-1 - Shimeng Wang; Xiangjian Wang; Jun Sun; Jin Yang; Deyang Wu; Fanglong Wu; Hongmei Zhou (Nature Publishing Group, 2023)
Abstract Oral squamous cell carcinoma (OSCC) escape from the immune system is mediated through several immunosuppressive phenotypes that are critical to the initiation and progression of tumors. As a hallmark of cancer, DNA damage repair is closely related to changes in the immunophenotypes of tumor cells. Although flap endonuclease-1 (FEN1), a pivotal DNA-related enzyme is involved in DNA base excision repair to maintain the stability of the cell genome, the correlation between FEN1 and tumor immunity has been unexplored. In the current study, by analyzing the clinicopathological characteristics of FEN1, we demonstrated that FEN1 overexpressed and that an inhibitory immune microenvironment was established in OSCC. In addition, we found that downregulating FEN1 inhibited the growth of OSCC tumors. In vitro studies provided evidence that FEN1 knockdown inhibited the biological behaviors of OSCC and caused DNA damage. Performing multiplex immunohistochemistry (mIHC), we directly observed that the acquisition of critical immunosuppressive phenotypes was correlated with the expression of FEN1. More importantly, FEN1 directly or indirectly regulated two typical immunosuppressive phenotype-related proteins human leukocyte antigen (HLA-DR) and programmed death receptor ligand 1 (PD-L1), through the interferon-gamma (IFN-γ)/janus kinase (JAK)/signal transducer and activator transcription 1 (STAT1) pathway. Our study highlights a new perspective on FEN1 action for the first time, providing theoretical evidence that it may be a potential immunotherapy target for OSCC.